2021
DOI: 10.3390/pr9091560
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Continuous PHA Production by a Hybrid Approach Based on First Principles and Machine Learning

Abstract: Polyhydroxyalkanoates (PHA) are renewable alternatives to traditional oil-derived polymers. PHA can be produced by different microorganisms in continuous culture under specific media composition, which makes the production process both promising and challenging. In order to achieve large productivities while maintaining high yield and efficiency, the continuous culture needs to be operated in the so-called dual nutrient limitation condition, where both the nitrogen and carbon sources are kept at very low conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Production of Poly-β-hydroxybutyrate (PHB) by Ralstonia Eutropha has been addressed by Patnaik et al ( 2008) [41] . The authors demonstrated the superiority of the hybrid model Putida GPo1 [42] . The hybrid model was shown to describe the process in a wide range of operating conditions, including single and dual nutrient-limited growth conditions.…”
Section: Microbial Culturementioning
confidence: 97%
“…Production of Poly-β-hydroxybutyrate (PHB) by Ralstonia Eutropha has been addressed by Patnaik et al ( 2008) [41] . The authors demonstrated the superiority of the hybrid model Putida GPo1 [42] . The hybrid model was shown to describe the process in a wide range of operating conditions, including single and dual nutrient-limited growth conditions.…”
Section: Microbial Culturementioning
confidence: 97%
“…The study of Saboe et al [134] effectively correlated microbial photoelectrosynthesis (MPS) signals with high algae concentrations in an algal cultivation pond, demonstrating the viability of using AI/ML in the monitoring and controlling microalgae cultivation processes via strong linear correlations and low normalized root mean square error (NRMSE) values. Through the integration of ML with real-time monitoring systems, potential disturbances in microalgae cultivation can be identified and corrected promptly, ensuring a steady and highquality bioplastic production [135].…”
Section: Potential Of Machine Learning In the Production Of Algal Bio...mentioning
confidence: 99%
“…First, multiple experimental data sets are simultaneously fitted to the mechanistic model. In a refitting exercise, the parameters related to growth, uptake, and product formation rates are independently estimated for each data set while leaving other parameters at their global estimates (Luna et al, 2021). The simulated states can be used to calculate the specific rates using the model equations, and this compilation can subsequently be used to train the data-driven components of the hybrid model.…”
Section: Direct Approachmentioning
confidence: 99%
“…The constraints imposed by conservation equations ensure the robustness (Tsopanoglou & Jiménez del Val, 2021), and prediction accuracy of hybrid models in an identified valid domain (Bae et al, 2020). Automated identification of data‐driven architecture reduces the expertise required for the parametric representation of the mechanistic part (Lopes Dias et al, 2007; Luna et al, 2021). Increased process knowledge from hybrid modeling when combined with the design of experiments (DoE), can reduce the experimental burden and accelerate process development (Bayer et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%